Coherent multidimensional spectroscopy of dilute gas-phase nanosystems - Lukas Bruder (Nature Portfolio, 2018)
Coherent multidimensional spectroscopy has greatly advanced our understanding of molecular dynamics but was so far broadly limited to complex condensed phase probes. Bruder et al. extend the method to isolated nanosystems in the gas phase and study cold molecules in a superfluid helium environment.